1992
DOI: 10.1161/01.hyp.19.6.634
|View full text |Cite
|
Sign up to set email alerts
|

Defective dopamine generation from dihydroxyphenylalanine in stable essential hypertensive patients.

Abstract: We studied the metabolic pathways of dihydroxyphenylalanine (DOPA) and dopamine as well as the cardiovascular and renal responses to a single administration of DOPA (500 mg orally) in stable essential hypertension. We found that after DOPA, stable hypertensive patients compared with controls showed more blood pressure decrease without reflex tachycardia, had lower creatinine clearance but a higher fractional excretion of sodium, and had lower plasma renin activity at the height of DOPA action. Hypertensive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…9,10 The aging kidney undergoes structural changes that result in quantitative alterations in some renal functions such as decline in renal blood flow and glomerular filtration rate. 11 High blood pressure or edema formation may be linked to abnormalities in the function of the renal dopaminergic system, such as decreased ability to synthesize dopamine 12,13 and deficient coupling of dopamine receptors to effector mechanisms. 6,14 -16 Despite their normal blood pressure, an increasing number of studies have revealed that old rats may present particular deficiencies in the renal handling of L-DOPA, its subsequent conversion to dopamine, 17,18 and at the level of receptor number or coupling to G proteins.…”
mentioning
confidence: 99%
“…9,10 The aging kidney undergoes structural changes that result in quantitative alterations in some renal functions such as decline in renal blood flow and glomerular filtration rate. 11 High blood pressure or edema formation may be linked to abnormalities in the function of the renal dopaminergic system, such as decreased ability to synthesize dopamine 12,13 and deficient coupling of dopamine receptors to effector mechanisms. 6,14 -16 Despite their normal blood pressure, an increasing number of studies have revealed that old rats may present particular deficiencies in the renal handling of L-DOPA, its subsequent conversion to dopamine, 17,18 and at the level of receptor number or coupling to G proteins.…”
mentioning
confidence: 99%
“…45 It is therefore of interest to compare these patterns to those observed in human hypertension subdivided into borderline and stable. We see in younger borderline hypertensive patients age-matched increases of urinary free DA 46 and 3-MT excretions 47 followed by normal 3-MT 48 or lower furosemide stimulated urinary DA excretion and natriuresis in older age-matched stable hypertensive patients. 46 Probably compensatory hyperdopaminergic patterns in initial stages of hypertension, subsequently confirmed in SHR 49 and in young borderline hypertensive patients, 50 are associated with a decreased natriuretic response to exogenous DA in SHR.…”
Section: Experimental Evidencementioning
confidence: 69%
“…66 Furthermore, a hypernatriuresis and excessive blood pressure decline in response to DOPA was observed in stable hypertensive patients despite their lower DA generation from DOPA. 48 The urinary cyclic AMP hyperresponsiveness to DA infusion in these patients 67 is also compatible with an upregulation of the adenyl-cyclase component of the DA 1 -like receptor. Since salt sensitivity exists in normotensive subjects and may be heritable, it is conceivable that it can precede the appearance of hypertension.…”
Section: Dopamine In Essential Hypertensionmentioning
confidence: 76%
See 2 more Smart Citations